Sintesis Membran Molecularly Imprinted Polymers (MIPs) dengan Metoda Photopolimerisasi sebagai Bahan Penyerap Glukosa - Pihanda, Febi Aulia; Ulianas, Alizar (Periodic, 2019)
MIPs are specific molecular identification polymer molds that are sensitive to their template molecules. The purpose of this discussion is to find out how to synthesize and characterize glucose MIPs membranes, optimum conditions for absorption of MIPs against glucose and application of Glucose MIPs. Based on literature, MIPs resulting from synthesis have a physical form in the form of solids. FTIR test results on MIPs are good, namely the appearance of O-H groups that indicate the presence of hydrogen bonds that can bind the template molecule in the form of glucose, in this discussion appears at wave number 3483,56 cm-1. The absorption capacity of MIPs for glucose can be influenced by the amount of MIPs, pH of glucose solution. Besides MIPs can be used to absorb glucose from the urine.